Antiepileptic properties of Quinine: A systematic review - Clifford, Mwita (Indian Academy of Neurosciences, 2012)
BACKGROUND: Quinine has anti-epileptic properties in animals. However, in humans this has not been systematically investigated. PURPOSE: To examine the available research evidence on the effects of quinine on seizures in adults or children. METHODS: We searched online databases for published and unpublished studies in any language from January 1966 to March 2011. We considered randomized controlled trials (RCTs) evaluating the use of quinine in comparison to other drugs in humans with malaria or other conditions, and that reported the prevalence of seizures. Random effects meta-analysis was used to pool effect estimates in order to determine the effect of quinine on the prevalence of seizures. RESULTS: We identified six randomized controlled trials on severe malaria. Quinine was compared to the artemisinin derivatives in all trials. A total of 8,244 patients were included. In the meta-analysis, there was no significant effect of quinine on the prevalence of seizures when compared to the artemisinin derivatives (Odds ratio (OR) =0.90, 95% Confidence Interval (95%CI) =0.63-1.30). There was significant heterogeneity (I(2)=66%, Chi-square=17.44, p=0.008). Subgroup analysis showed that quinine significantly reduced seizures when compared to artemether (OR = 0.66, 95%CI = 0.49-0.88) but when compared to artesunate, prevalence of seizures increased significantly (OR = 1.24, 95%CI = 1.05-1.47). CONCLUSION: There is no sufficient evidence to conclude that quinine has any antiepileptic properties in humans.